Analysis of the Impact of Excellent Service on Visitor Satisfaction: (A Study at The Bagong Adventure Human Body Museum) - da Silva, Jose; Zunaida, Daris; Deka, Rio Era (International Journal of Social Science and Community Service, 2024)
This research aims to assess the individual and combined impacts of ability, attitude, appearance, attention, action, and responsibility on visitor satisfaction using quantitative methods. The study population was selected through accidental sampling. Data analysis was conducted using multiple linear regression analysis with the IBM SPSS Statistics software. The findings reveal that ability, attitude, appearance, and attention have a significant partial effect on visitor satisfaction, whereas action and responsibility do not significantly impact visitor satisfaction. This is due to the action variable having a significance level of 0.550 > 0.05 and the responsibility variable having a significance level of 0.171 > 0.05. When considered together, the F test significance value of 0.001 is less than the predetermined significance level of ? = 5%, and the 73% coefficient of determination indicates the extent of influence of the independent variables on the dependent variable, with other factors affecting visitor satisfaction beyond the researcher's scope accounting for 23%.